(untitled) - Thompson, F G (London, 1992)
The book covers material of a more advanced technical nature reflecting the type of work expected of installation technicians in electrical contracting and industrial maintenance. The emphasis is on the application of electrical knowledge and experience in practical situations encoutered in commercial and industrial premises. In this book additional information on the application and utilization of electricity, and its associated economic material on machines and their applications
Keywords: Electrical engineering,Electronics